Seizing Local Wisdom: Looking Closer Into Javanese Folklore Through Jamasan Keris Ritual - Herminingrum, Sri; Majid, Gilang Maulana (Institute of Research and Community Service, University of Brawijaya, 2016)
The myriad of folklores in Indonesia is a vast area to study. Jamasan Keris ritual as one of the embodiment of Javanese folklore, however, still invites many questions in accordance with the local values. Therefore, this paper tries to disclose the research result executed in two villages, Margomulyo and Karangtengah, in Ngawi regency of which Jamasan Keris held as sacred ritual. Jamasan Keris in these areas is selected as the object of the study for it serves Javanese traditional values. Moreover, ethnography approach is used in this study to get accurate result based on the knowledge of the informants who are Javanists. Direct field observation, at the same time, is conducted to highlight the required data. From the result of this scholarly work, it can be inferred that the values of Jamasan Keris ritual consists of two factors: (1) how Javanese involving in folk culture give spiritual meaning to the existed tradition, and (2) how Javanese deep philosophies encourage the traditional people to keep on preserving their culture. To sum up, the long-living spiritual meaning behind tradition and philosophical content in ritual are the underpinning of local wisdom.Keywords: Javanese folklore, Jamasan Keris ritual, traditional values, Javanists, local wisdom